Hard carbon material and preparation method and application thereof

By using porous hard carbon materials, non-porous hard carbon materials and nano-sized solid electrolytes in hard carbon materials, the problem of hard carbon materials being difficult to achieve both compaction density and specific capacity in sodium ion batteries is solved, and hard carbon materials with high compaction density and good kinetic performance are achieved, which improves the volume energy density of sodium ion batteries.

CN119650663APending Publication Date: 2025-03-18SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411951026.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

It is difficult to obtain both the compaction density and specific capacity of hard carbon materials in sodium ion batteries, resulting in a decrease in volume energy density.

Method used

The synergistic effects of porous hard carbon materials, non-porous hard carbon materials and nano-sized solid electrolytes are adopted to improve the compaction density and kinetic properties of hard carbon materials by adjusting the mass ratio and particle size differences of each component.

Benefits of technology

While maintaining capacity, hard carbon materials with high compaction density and good kinetic properties are obtained, which improves the volume energy density of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650663A_ABST
    Figure CN119650663A_ABST
Patent Text Reader

Abstract

The invention provides a hard carbon material and a preparation method and application thereof. The hard carbon material comprises secondary particles, and the materials of the secondary particles comprise a porous hard carbon material, a non-porous hard carbon material and a nanocrystallization solid electrolyte; and the shell layer is coated on the surfaces of the secondary particles. The porous hard carbon material in the hard carbon material has a large number of closed pores and can provide rich sodium storage sites; gaps of the porous hard carbon material are filled with the non-porous hard carbon to improve the compaction density of the material, and the nanocrystallization solid electrolyte is doped to improve the overall ionic conductivity and dynamic performance of the secondary particles; based on the synergistic effect among the porous hard carbon material, the nonporous hard carbon material and the nanocrystallization solid electrolyte, the prepared sodium-ion battery negative electrode plate can reach high compaction density, and the sodium-ion battery can have good dynamic performance on the premise of keeping the capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy, and in particular relates to a hard carbon material and a preparation method and application thereof. Background Art

[0002] The successful commercialization of lithium-ion batteries is inseparable from the development of graphite negative electrode materials. Similarly, for sodium-ion batteries to be commercialized, a negative electrode material with excellent performance and low cost must be developed. Graphite cannot be embedded in sodium-ion batteries due to its low interlayer spacing. Soft carbon lacks a microporous structure inside. Although the rate performance is good, the capacity is low. Hard carbon materials have a reversible capacity of more than 300 mAh / g due to their larger interlayers and rich closed-pore pore structure. However, the rich closed pore structure of hard carbon materials leads to a significant decrease in the compaction density of the material, thereby reducing the volume energy density of sodium-ion batteries. Although the compaction density of the material can be improved to a certain extent by reducing the closed pores, it will lead to a decrease in the active sodium storage sites of the material, and a decrease in the capacity and sodium ion migration rate. It can be seen that it is difficult to achieve both compaction density and specific capacity in hard carbon negative electrode materials. Summary of the invention

[0003] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions: One of the objects of the present invention is to provide a hard carbon material, comprising: Secondary particles, wherein the materials of the secondary particles include porous hard carbon materials, non-porous hard carbon materials and nano-sized solid electrolytes; The shell layer is coated on the surface of the secondary particles.

[0004] The porous hard carbon material in the hard carbon material has a large number of closed pores, which can provide abundant sodium storage sites; the non-porous hard carbon material is filled between the voids of the porous hard carbon material, which can improve the compaction density of the material. Since the low sodium ion mobility of the non-porous hard carbon material will affect the kinetic properties of the material, a nano-sized solid electrolyte is incorporated therein to improve the overall ionic conductivity and kinetic properties of the secondary particles, and the nano-sized solid electrolyte also helps to synergistically improve the compaction density with the non-porous hard carbon material. By utilizing the synergistic effect between the porous hard carbon material, the non-porous hard carbon material and the nano-sized solid electrolyte, a hard carbon material with a high compaction density and good kinetic properties can be obtained while maintaining the capacity. The hard carbon material also has a shell layer coated on the surface of the secondary particles, which is used to fill the pores of the porous hard carbon material and improve the capacity and the first effect.

[0005] In some embodiments, the mass ratio of the porous hard carbon material, the non-porous hard carbon material and the nano-sized solid electrolyte is (80~95): (1~5): (1~3). The mass ratio of the porous hard carbon material, the non-porous hard carbon material and the nano-sized solid electrolyte has a certain influence on the comprehensive performance of the hard carbon material. If the content of the nano-sized solid electrolyte is too low, the improvement of the ionic conductivity and kinetic performance is not significant. If the content of the nano-sized solid electrolyte is too high, the capacity of the material will be reduced. If the content of the non-porous hard carbon material is too high, the ion mobility of the hard carbon material will be reduced. If its content is too low, the compaction density of the material will be reduced.

[0006] In some embodiments, the porous hard carbon material and the non-porous hard carbon material are both micrometer-sized, and the particle size of the porous hard carbon material is larger than that of the non-porous hard carbon material. The combination of the particle size difference between the large-particle porous hard carbon material, the small-particle non-porous hard carbon material and the nano-sized solid electrolyte helps to obtain an electrode material with a higher compaction density.

[0007] In some preferred embodiments, the median particle size D50 of the porous hard carbon material is 5-15 um, such as 7um, 10um, 12um, etc.; the median particle size D50 of the non-porous hard carbon material is 1-3μm, such as 1μm, 2μm, 3μm.

[0008] In some embodiments, the porosity of the porous hard carbon material is 10-30%, for example, 10%, 15%, 20%, 25%, or 30%.

[0009] In some embodiments, the porosity of the non-porous hard carbon material is less than 5%, such as 4%, 3%, 2%, 1% or less.

[0010] In some embodiments, the intensity ratio of the D peak to the G peak in the Raman spectrum of the porous hard carbon material is greater than 1.1, and the intensity ratio of the D peak to the G peak in the Raman spectrum of the non-porous hard carbon material is less than 1.1. The porous hard carbon material has a large intensity ratio of the D peak to the G peak and a high degree of disorder, so it has a high ion transmission rate; the non-porous hard carbon material has a low degree of disorder, so it has a high electron transmission rate, and the two work together to make the hard carbon material have good ion and electron transmission performance.

[0011] In some embodiments, the specific surface area of ​​the porous hard carbon material is 10-30 m 2 / g.

[0012] In some embodiments, the non-porous hard carbon material has a specific surface area of ​​2 to 5 m 2 / g.

[0013] The porous hard carbon material and non-porous hard carbon material can be obtained through commercial channels, or can be prepared according to existing disclosed preparation methods.

[0014] Exemplarily, the preparation method of the porous hard carbon material can be: mixing biomass materials (such as walnut shells, coconut shells, bamboo powder, wood powder, etc.) with pore-forming agents (such as calcium gluconate, magnesium gluconate, etc.) in a mass ratio of 10:2-10, carbonizing at 400-700°C, crushing to the target particle size, and then acid washing and drying.

[0015] Exemplarily, the method for preparing the non-porous hard carbon material may be: directly carbonizing the biomass raw material at 400-700° C., crushing it to a target particle size, and then acid washing and drying it.

[0016] In some embodiments, the median particle size D50 of the nano-sized solid electrolyte is 50-300 nm, for example, 100 nm, 200 nm, 250 nm. If the particle size of the nano-sized solid electrolyte is too large, the compaction density of the material will be reduced, and the contact area with the small particle non-porous hard carbon material will be reduced, thereby reducing the ionic conductivity.

[0017] In some embodiments, the nanostructured solid electrolyte includes a sodium ion solid electrolyte.

[0018] In some preferred embodiments, the sodium ion solid electrolyte includes a NASICON solid electrolyte. Compared with other types of solid electrolytes, the NASICON solid electrolyte not only has high sodium ion conductivity, but also the Zr element therein can change from tetravalent to trivalent during the charge and discharge process, and form a high-conductivity SEI layer with the electrolyte during the reduction reaction, thereby stabilizing the interface and improving ion transmission.

[0019] In some preferred embodiments, the sodium ion solid electrolyte comprises , where 1≤x≤3.

[0020] In some embodiments, the ratio of the diameter of the secondary particle to the thickness of the shell layer is 100-90:1-10.

[0021] In some embodiments, the diameter of the secondary particles is 5-15 um, for example, 6 um, 8 um, 10 um, 12 um, etc.

[0022] In some embodiments, the thickness of the shell layer is 10-100 nm, such as 20 nm, 40 nm, 60 nm, 80 nm, etc.

[0023] In some embodiments, the raw material for forming the shell layer includes one or more of asphalt, phenolic resin, and starch, but is not limited thereto. The shell layer formed by these raw materials can transform the open pores on the surface of the hard carbon material into closed pores.

[0024] A second object of the present invention is to provide a method for preparing a hard carbon material, comprising: Carrying out a carbonization granulation treatment on a uniform first mixed material containing a porous hard carbon material, a non-porous hard carbon material, a nano-sized solid electrolyte and a binder to obtain secondary particles; Stirring a uniform second mixed material containing the secondary particles, the coating material and the organic solvent for a preset time so that the coating material is coated on the secondary particles, thereby forming a shell layer on the surface of the secondary particles to obtain an intermediate material; In an inert atmosphere, the intermediate material is subjected to a multi-stage carbonization treatment, wherein the multi-stage carbonization treatment includes subjecting the intermediate material to a primary carbonization and a secondary carbonization in sequence, and the temperatures of the primary carbonization and the secondary carbonization are gradually increased, thereby forming a hard carbon material.

[0025] In some embodiments, the temperature of the primary carbonization is 150-300° C., and the temperature of the secondary carbonization is 1000-1500° C. The multi-stage carbonization method can improve the carbonization degree of the material and the uniformity of the coating layer.

[0026] In some embodiments, the primary carbonization time is 1 to 3 hours, and the secondary carbonization time is 3 to 5 hours.

[0027] In some embodiments, the carbonization granulation includes carbonizing the first mixed material at 150-250° C. for 1-3 hours.

[0028] In some embodiments, the stirring time is 6 to 24 hours, so that the coating material can be evenly and fully coated on the surface of the material.

[0029] In some embodiments, the mass ratio of the porous hard carbon material, the non-porous hard carbon material, and the nano-sized solid electrolyte in the first mixed material is (80-95): (1-5): (1-3). Specifically, the mass concentrations of the porous hard carbon material, the non-porous hard carbon material, and the nano-sized solid electrolyte in the first mixed material may be 80-95wt%, 1-5wt%, and 1-3wt%, respectively.

[0030] In some embodiments, the content of the binder in the first mixed material is 1-5wt%. The binder can be PVDF, PTFE, CMC or other existing binders in the art, which is not particularly limited in the present invention.

[0031] In some embodiments, the mass ratio of the secondary particles to the coating material in the second mixed material is 100-90:1-5.

[0032] In some embodiments, the organic solvent includes one or a combination of more of toluene, tetrahydrofuran, and formaldehyde, but is not limited thereto.

[0033] In some embodiments, the coating material includes one or a combination of asphalt, phenolic resin, starch, but is not limited thereto.

[0034] In some embodiments, the porous hard carbon material and the non-porous hard carbon material are both in micron size, and the particle size of the porous hard carbon material is larger than that of the non-porous hard carbon material.

[0035] In some preferred embodiments, the median particle size D50 of the porous hard carbon material is 5-15 um, and the median particle size D50 of the non-porous hard carbon material is 1-3 μm.

[0036] In some embodiments, the porosity of the porous hard carbon material is 10-30%.

[0037] In some embodiments, the non-porous hard carbon material has a porosity of less than 5%.

[0038] In some embodiments, the intensity ratio of the D peak to the G peak in the Raman spectrum of the porous hard carbon material is greater than 1.1, and the intensity ratio of the D peak to the G peak in the Raman spectrum of the non-porous hard carbon material is less than 1.1.

[0039] In some embodiments, the specific surface area of ​​the porous hard carbon material is 10-30 m 2 / g.

[0040] In some embodiments, the non-porous hard carbon material has a specific surface area of ​​2 to 5 m 2 / g.

[0041] In some embodiments, the median particle size D50 of the nano-sized solid electrolyte is 50-300 nm.

[0042] In some embodiments, the nanostructured solid electrolyte includes a sodium ion solid electrolyte.

[0043] In some preferred embodiments, the sodium ion solid electrolyte includes a NASICON-type solid electrolyte.

[0044] In some preferred embodiments, the sodium ion solid electrolyte comprises , where 1≤x≤3.

[0045] In a typical embodiment, the method for preparing the hard carbon material comprises: (1) A porous hard carbon material with a median particle size D50 of 5 to 15 μm, a non-porous hard carbon material with a median particle size D50 of 1 to 3 μm, a nano-sized solid electrolyte with a median particle size D50 of 50 to 300 nm, and a binder are mixed to obtain a first mixed material, and the first mixed material is carbonized and granulated to obtain secondary particles; (2) uniformly dispersing the coating material in an organic solvent to obtain a coating liquid, mixing the secondary particles with the coating liquid to obtain a second mixed material, stirring for a preset time and then drying to obtain an intermediate material; (3) In an inert atmosphere, the intermediate material is carbonized. The carbonization treatment is a two-stage carbonization in a temperature zone. The first stage carbonization temperature is 150-300 degrees Celsius for 1-3 hours. The second stage carbonization temperature is 1000-1500 degrees Celsius for 3-5 hours, thereby obtaining a hard carbon material.

[0046] A third object of the present invention is to provide a hard carbon material prepared by any of the methods described above.

[0047] A fourth object of the present invention is to provide a sodium ion battery negative electrode, the sodium ion battery negative electrode comprising a current collector and a negative electrode active material layer formed on the current collector, the negative electrode active material layer comprising any one of the hard carbon materials described.

[0048] In some embodiments, the negative electrode slurry for forming the negative electrode active material layer includes a negative electrode active material, a conductive agent, and a binder, wherein the negative electrode active material includes the hard carbon material.

[0049] In some embodiments, the mass ratio of the negative electrode active material, the conductive agent and the binder is (90-100): (0-5): (0-5). The conductive agent and the binder used can be any one or more of the existing conductive agents and binders, such as carbon black for the conductive agent and sodium carboxymethyl cellulose for the binder, and the present invention does not specifically limit this.

[0050] The negative electrode sheet prepared based on the hard carbon material has a high compaction density. In some embodiments, the compaction density can reach 1.05 g / cm 3 above.

[0051] A fifth object of the present invention is to provide a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode is the negative electrode of the sodium ion battery.

[0052] Compared with the prior art, the present invention has at least the following beneficial effects: (1) The secondary particles of the hard carbon material provided by the present invention contain porous hard carbon material, non-porous hard carbon material and nano-sized solid electrolyte. The porous hard carbon material has a large number of closed pores, which can provide abundant sodium storage sites. The non-porous hard carbon material is filled in the gaps between the porous hard carbon material to improve the compaction density of the material. The nano-sized solid electrolyte can not only improve the overall ionic conductivity and kinetic performance of the secondary particles, but also cooperate with the non-porous hard carbon material to improve the compaction density of the negative electrode sheet. The compaction density of the negative electrode sheet is improved by selecting large-particle porous hard carbon, small-particle porous hard carbon and nano-sized solid electrolyte with appropriate particle sizes and cooperating with each other in terms of particle size difference.

[0053] (2) The sodium ion battery negative electrode sheet provided by the present invention has a high compaction density, and the assembled sodium ion battery can have good kinetic performance while maintaining capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0055] Figure 1 is a SEM image of secondary particles prepared in Example 1 of the present invention; Figure 2 is an EDS C-scan image of the secondary particles prepared in Example 1 of the present invention; Figure 3 is an EDS Si scanning image of the secondary particles prepared in Example 1 of the present invention; Figure 4 This is the Zr scanning graph of the EDS of the secondary particles prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0056] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0057] In addition, unless otherwise specified, the various raw materials used in the following examples can be purchased from the market, and the various production and testing equipment used are equipment known in the art. The testing methods used are conventional methods commonly used by those skilled in the art.

[0058] Example 1

[0059] The preparation method of the porous hard carbon material used in this embodiment is: walnut shells and pore-forming agent calcium gluconate are mixed in a mass ratio of 10:5, and then carbonized at 600° C. for 2 hours, crushed to a target particle size, acid-washed and dried for later use.

[0060] The preparation method of the non-porous hard carbon material adopted in this embodiment is: carbonizing the walnut shell at a temperature of 600° C. for 2 hours, then crushing the carbonized product to a target particle size, acid washing and drying, and setting aside.

[0061] The solid electrolyte used in this embodiment is .

[0062] The relevant characteristics of the above-mentioned porous hard carbon material, non-porous hard carbon material and nano-solid electrolyte are shown in Table 1: Table 1

[0063] In Table 1, D50 means: the volume distribution of particles smaller than this particle size in the particle size tester reaches 50%.

[0064] The porosity test method in Table 1 is: by measuring the isothermal adsorption-desorption curve of nitrogen / CO2, the total pore volume of the material and the true volume of the sample are determined, and then the porosity is calculated. The test sample is the finished material after secondary sintering.

[0065] This embodiment provides a hard carbon material and a preparation method thereof, which specifically includes the following steps: The porous hard carbon material, the non-porous hard carbon material and the nano-sized solid electrolyte are mixed in a mass ratio of 93:4:3, and a binder PVDF is added, and the mixture is uniformly mixed by a wet mixing method to obtain a first mixed material, wherein the mass of PVDF is 5% of the total mass of the first mixed material; the first mixed material is carbonized at 200° C. for 1 hour to form secondary particles; Dispersing asphalt in tetrahydrofuran solvent to obtain a coating liquid, and adding the secondary particles prepared above to the coating liquid to form a second mixed material, wherein the mass ratio of the secondary particles to the asphalt is 100:5, mixing and stirring for 3 hours to coat the asphalt on the surface of the secondary particles, and then drying at 120°C to obtain an intermediate material; The intermediate material was first carbonized at 200°C for 2 hours, and then heated to 1200°C for carbonization for 4 hours to obtain a hard carbon material.

[0066] Figure 1 is a SEM image of the secondary particles prepared in this example. Figure 2 is the EDS C-scan image of the secondary particles prepared in this example, Figure 3 is the Si scan of the EDS of the secondary particles; Figure 4 This is the EDS Zr scan of the secondary particles.

[0067] Example 2 The porous hard carbon material, non-porous hard carbon material, nano-sized solid electrolyte and asphalt used in Example 2 are the same as those used in Example 1, except that: In Example 2, the mass ratio of the porous hard carbon material, the non-porous hard carbon material, and the nano-sized solid electrolyte is 80:5:2; The multi-stage carbonization process is as follows: the intermediate material is first carbonized at 150° C. for 3 h, and then heated to 1000° C. for carbonization for 5 h to obtain a hard carbon material.

[0068] The rest is implemented in the same manner as in Example 1 and will not be described again.

[0069] Example 3 The porous hard carbon material, non-porous hard carbon material, nano-sized solid electrolyte and asphalt used in Example 3 are the same as those used in Example 1, except that: In Example 3, the mass ratio of the porous hard carbon material, the non-porous hard carbon material, and the nano-sized solid electrolyte is 95:5:1; The multi-stage carbonization process is as follows: firstly, the mixed material is carbonized at 300°C for 3 hours, and then the temperature is raised to 1500°C and carbonized for 3 hours to obtain a hard carbon material.

[0070] Example 4 The preparation method of the porous hard carbon material used in this embodiment is: coconut shell and pore-forming agent calcium gluconate are mixed in a mass ratio of 10:2, and then carbonized at 500° C. for 2 hours, crushed to a target particle size, acid-washed and dried for later use.

[0071] The preparation method of the non-porous hard carbon material used in this embodiment is as follows: carbonizing the coconut shell at 600° C. for 2 h, crushing it to a target particle size, acid washing and drying it for later use.

[0072] The solid electrolyte used in this embodiment is , sand grind to target particle size and set aside.

[0073] The relevant characteristics of the above-mentioned porous hard carbon material, non-porous hard carbon material and nano-solid electrolyte are shown in Table 2: Table 2

[0074] The hard carbon material is prepared using the above-mentioned porous hard carbon material, non-porous hard carbon material and nano-sized solid electrolyte. The preparation method is basically the same as that in Example 1. The only difference is that the coating material asphalt in Example 1 is replaced by phenolic resin. The rest is implemented in the same way as Example 1 and will not be repeated here.

[0075] Example 5 The preparation method of the porous hard carbon material used in this embodiment is: the biomass raw material bamboo powder and the pore-forming agent magnesium gluconate are mixed in a ratio of 1:1, and then carbonized at 500 degrees for 2 hours, crushed to the target particle size, and then acid-washed and dried.

[0076] The preparation method of the non-porous hard carbon material is as follows: the biomass raw material bamboo powder is directly carbonized at 700 degrees, crushed to a target particle size, and then acid-washed and dried.

[0077] The solid electrolyte used in this embodiment is , sand grind to the target particle size and set aside.

[0078] The relevant characteristics of the above-mentioned porous hard carbon material, non-porous hard carbon material and nano-solid electrolyte are shown in Table 3: Table 3

[0079] The hard carbon material is prepared using the above-mentioned porous hard carbon material, non-porous hard carbon material and nano-sized solid electrolyte. The preparation method is basically the same as that in Example 1. The only difference is that the coating material asphalt in Example 1 is replaced by starch. The rest is implemented in the same way as Example 1 and will not be repeated here.

[0080] Example 6 Example 6 is basically the same as Example 1, except that the solid electrolyte in Example 1 is replaced by Replace with The rest is implemented in the same way as in Example 1 and will not be described again.

[0081] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the nano-sized solid electrolyte is not used, and the rest is implemented in the same way as Example 1, which will not be repeated here.

[0082] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that no non-porous hard carbon material is used, and the rest is implemented in the same way as Example 1, which will not be repeated here.

[0083] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that in the first mixed material, the porous hard carbon material, the non-porous hard carbon material and the nano-sized solid electrolyte are mixed in a mass ratio of 85:3:5, and the rest is implemented in the same way as Example 1, which will not be repeated here.

[0084] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that in the first mixed material, the mass ratio of the porous hard carbon material, the non-porous hard carbon material, and the nano-sized solid electrolyte is 85:8:1, and the rest is implemented in the same way as Example 1, which will not be repeated here.

[0085] Comparative Example 5 The porous hard carbon material, non-porous hard carbon material and nano-sized solid electrolyte used in Comparative Example 5 are the same as those in Example 1.

[0086] The porous hard carbon material and the non-porous hard carbon material are mixed in a mass ratio of 85:3, and a binder PVDF is added, and the mixture is uniformly mixed by a wet mixing method to obtain a first mixed material, wherein the mass of the PVDF is 5% of the total mass of the first mixed material; the first mixed material is carbonized at 200° C. for 1 hour to form secondary particles; The asphalt and the nano-sized solid electrolyte are dispersed in a tetrahydrofuran solvent to obtain a coating liquid, and the secondary particles prepared above are added to the coating liquid to form a second mixed material, wherein the mass ratio of the secondary particles, the asphalt and the nano-sized solid electrolyte is 93:4:3, and the mixture is stirred for 3 hours so that the asphalt and the nano-sized solid electrolyte are coated on the surface of the secondary particles, and then dried at 120°C to obtain an intermediate material; The intermediate material is first carbonized at 200°C for 2 hours, then heated to 600°C for carbonization for 2 hours, and then heated to 1200°C for carbonization for 4 hours to obtain a hard carbon material.

[0087] The hard carbon material was used to prepare the negative electrode: the hard carbon material, the conductive agent carbon black and the binder sodium carboxymethyl cellulose were mixed in a mass percentage of 91:3:6, and deionized water was added to adjust the solid content to 50wt%, and the mixture was evenly coated on the copper foil current collector, vacuum dried, and rolled to a surface density of 5.5±0.5mg / cm 2 , cut into 14mm pieces with a puncher to obtain a negative electrode sheet. The compaction density of the obtained negative electrode sheet was tested, and the test results are shown in Table 4: Table 4 Compacted density of negative electrode sheets prepared using hard carbon materials in Examples and Comparative Examples

[0088] In Table 4, the compaction density of the pole piece = (total mass of the pole piece - mass of the copper foil) / (area of ​​the pole piece with a diameter of 14 mm * thickness of the pole piece).

[0089] The above negative electrode sheet was used to assemble a sodium ion battery, a 16 mm sodium sheet was used as the counter electrode, 1 mol / L NaPF6 / DIGLYME (100 Vol%) was used as the electrolyte, the separator was glass fiber, and a 2032 button battery shell was used to assemble a button half-cell. The relevant performance of the obtained sodium ion battery was tested, and the test results are shown in Table 5.

[0090] Table 5 Sodium ion battery related performance

[0091] According to Table 4, compared with Example 1 and Comparative Examples 1-2, the negative electrode sheet prepared by adding small-particle non-porous hard carbon material and hard carbon material obtained by nano-sized solid electrolyte has a higher compaction density. Compared with introducing solid electrolyte in the coating layer, introducing solid electrolyte in the secondary particles is more conducive to the improvement of compaction density, which may be due to the synergistic effect between solid electrolyte and small-particle non-porous hard carbon material. According to Table 5, the sodium ion battery that meets the technical solution of the present invention has better discharge specific capacity, first efficiency and capacity retention rate. Compared with Example 1 and Comparative Example 1 in Table 5, it can be seen that the introduction of solid electrolyte can also improve the ion transfer rate between the interface of non-porous hard carbon material and porous hard carbon material, thereby improving the rate performance of the battery.

[0092] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0093] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0094] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another element.

Claims

1. A hard carbon material, characterized in that: include: Secondary particles, wherein the materials of the secondary particles include porous hard carbon materials, non-porous hard carbon materials and nano-sized solid electrolytes; The shell layer is coated on the surface of the secondary particles.

2. The hard carbon material according to claim 1, characterized in that: The mass ratio of the porous hard carbon material, the non-porous hard carbon material and the nano-sized solid electrolyte is (80-95): (1-5): (1-3); And / or, the porous hard carbon material and the non-porous hard carbon material are both micrometer-sized, and the particle size of the porous hard carbon material is larger than that of the non-porous hard carbon material; preferably, the median particle size D50 of the porous hard carbon material is 5-15 um, and the median particle size D50 of the non-porous hard carbon material is 1-3 μm; and / or, the porosity of the porous hard carbon material is 10-30%; and / or, the porosity of the non-porous hard carbon material is less than 5%; and / or, the intensity ratio of the D peak to the G peak in the Raman spectrum of the porous hard carbon material is greater than 1.1, and the intensity ratio of the D peak to the G peak in the Raman spectrum of the non-porous hard carbon material is less than 1.1; And / or, the specific surface area of ​​the porous hard carbon material is 10-30 m 2 / g; And / or, the specific surface area of ​​the non-porous hard carbon material is 2-5 m 2 / g; And / or, the median particle size D50 of the nano-sized solid electrolyte is 50-300 nm; And / or, the nanostructured solid electrolyte comprises a sodium ion solid electrolyte, preferably comprises a NASICON type solid electrolyte, more preferably comprises , where 1≤x≤3.

3. The hard carbon material according to claim 1, characterized in that: The ratio of the diameter of the secondary particles to the thickness of the coating layer is 100-90:1-10; And / or, the diameter of the secondary particles is 5-15 um; And / or, the thickness of the shell layer is 10-100 nm; And / or, the raw material for forming the shell layer includes one or a combination of asphalt, phenolic resin, and starch.

4. A method for preparing a hard carbon material, characterized in that: include: Carrying out a carbonization granulation treatment on a uniform first mixed material containing a porous hard carbon material, a non-porous hard carbon material, a nano-sized solid electrolyte and a binder to obtain secondary particles; Stirring a uniform second mixed material containing the secondary particles, the coating material and the organic solvent for a preset time so that the coating material is coated on the secondary particles, thereby forming a shell layer on the surface of the secondary particles to obtain an intermediate material; In an inert atmosphere, the intermediate material is subjected to a multi-stage carbonization treatment, wherein the multi-stage carbonization treatment includes subjecting the intermediate material to a primary carbonization and a secondary carbonization in sequence, and the temperatures of the primary carbonization and the secondary carbonization are gradually increased, thereby forming a hard carbon material.

5. The preparation method according to claim 4, characterized in that: The carbonization granulation comprises carbonizing the first mixed material at 150-250° C. for 1-3 hours; And / or, the stirring time is 6 to 24 hours; And or, the temperature of the primary carbonization is 150-300°C, and the temperature of the secondary carbonization is 1000-1500°C; And / or, the time of the primary carbonization is 1 to 3 hours, and the time of the secondary carbonization is 3 to 5 hours.

6. The preparation method according to claim 4, characterized in that: The mass ratio of the porous hard carbon material, the non-porous hard carbon material and the nano-sized solid electrolyte in the first mixed material is (80-95): (1-5): (1-3); And / or, the content of the binder in the first mixed material is 1-5wt%; and / or, the mass ratio of the secondary particles to the coating material in the second mixed material is 100-90:1-5; And / or, the organic solvent includes one or a combination of toluene, tetrahydrofuran, and formaldehyde; And / or, the coating material includes one or a combination of asphalt, phenolic resin, and starch.

7. The preparation method according to claim 4, characterized in that: The porous hard carbon material and the non-porous hard carbon material are both micron-sized, and the particle size of the porous hard carbon material is larger than that of the non-porous hard carbon material; preferably, the median particle size D50 of the porous hard carbon material is 5-15 um, and the median particle size D50 of the non-porous hard carbon material is 1-3 μm; and / or, the porosity of the porous hard carbon material is 10-30%; and / or, the porosity of the non-porous hard carbon material is less than 5%; and / or, the intensity ratio of the D peak to the G peak in the Raman spectrum of the porous hard carbon material is greater than 1.1, and the intensity ratio of the D peak to the G peak in the Raman spectrum of the non-porous hard carbon material is less than 1.1; And / or, the specific surface area of ​​the porous hard carbon material is 10-30 m 2 / g; And / or, the specific surface area of ​​the non-porous hard carbon material is 2-5 m 2 / g, And / or, the median particle size D50 of the nano-sized solid electrolyte is 50-300 nm; And / or, the nanostructured solid electrolyte comprises a sodium ion solid electrolyte, preferably comprises a NASICON type solid electrolyte, more preferably comprises , where 1≤x≤3.

8. A hard carbon material, characterized in that: The method is prepared by the method described in any one of claims 4 to 7.

9. A sodium ion battery negative electrode, characterized in that: The invention comprises a current collector and a negative electrode active material layer formed on the current collector, wherein the negative electrode active material layer comprises the hard carbon material according to any one of claims 1 to 3 and 8.

10. A sodium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The negative electrode is the negative electrode of the sodium ion battery according to claim 9.